Empowering Local Governance: The Role of Data-Driven Decision-Making in Accelerating Rural Development - pahira, Siti Hapsah (Journal of Village Development Innovation, 2024)
Rural areas face unique governance challenges, including limited resources, infrastructure deficits, and varying community needs. This study investigates the role of data-driven decision-making in empowering rural governance to address these challenges and accelerate development. The objective is to develop an adaptable framework that enhances resource allocation, transparency, and local engagement. Employing a qualitative approach, data was collected through in-depth interviews with rural governance officials and document analysis. The findings reveal that while data integration is in the early stages, it has shown potential in improving project prioritization, budget efficiency, and community satisfaction. Significant barriers include resource constraints, technological infrastructure limitations, and a shortage of data literacy. Recommendations for enhancing data-driven governance in rural areas involve implementing training programs, increasing infrastructure investments, and fostering partnerships with external organizations. The study concludes that data-driven governance can bridge the urban-rural development gap, contributing to more balanced and sustainable growth.